Handbook of Thermoset Plastics. - Hanna, Dodiuk (Elsevier Science, 2013)
Thermosetting plastics are a distinct category of plastics whose high performance, durability and reliability at high temperatures makes them suitable for specialty applications ranging from automotive and aerospace through to electronic packaging and consumer products (your melamine kitchen worktop is a thermoset resin!). Recent developments in thermoset plastics technology and processes has broadened their use exponentially over recent years, and these developments continue: in November 2011, French scientists created a new lightweight thermoset that is as strong and stable as previous ma.